Zakotwiczanie się. Migrantki z Polski w norweskim przedszkolu - Izabela Czerniejewska (Problemy Wczesnej Edukacji)
Based on participant observation and ethnographic interviews with Polish women working in kin-dergartens in Norway, this article studies the migrant women’s employment trajectories, including adaptation processes in the workplace and integration into the wider Norwegian society. In this paper, I aim at answering the following questions: How do Polish migrant women go about seek-ing employment in Norwegian kindergartens? How do they adapt to the new work environment? How do they deal with cross-cultural differences in childcare? How did they learn new norms and values within the institutional context of kindergartens? The research indicates that employment in kindergartens was not merely a way to provide for one’s livelihood, but was also a mechanism to establish and develop a closer relationship with members of the Norwegian society, a tool facilitating meaningful connections with the new country.